2013
DOI: 10.5455/2320-1770.ijrcog20130935
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of recurrent uterine inversion requiring double reposition

Abstract: Acute puerperal uterine inversion is a rare but life threatening complication of third stage of labour. The incidence varies widely between 1 in 2000 to 1 in 50,000 deliveries, largely dependent upon the standard of management of the third stage of labour. Acute uterine inversion occurs within 24 hours delivery; subacute between 24 hours and 4 weeks of delivery and chronic uterine inversion after 4 weeks or in the non pregnant state. Cases of subacute and chronic uterine inversion require surgical management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…3,4 Kabir N et al and Sharma N et al have reported acute uterine inversion managed by Johnson's maneuver; then subacute uterine inversion by Haultain's operation (cervical ring is posteriorly incised to facilitate uterine replacement by Huntington method). 5,6 Another case report of successful management of recurrent puerperal uterine inversion was managed first by Jhonson's maneuver for acute inversion and for recurrent uterine inversion exploratory laparotomy was done to reposit by Huntington technique (progressive upward traction on each round ligament by application of atraumatic clamps with simultaneous upward pressure transvaginally) and multiple Cho suture; bilateral uterine arteries and utero ovarian arteries were ligated prophylactically. Vaginal pack with roller gauze kept prophylactically to prevent reinversion.…”
Section: Commentsmentioning
confidence: 99%
“…3,4 Kabir N et al and Sharma N et al have reported acute uterine inversion managed by Johnson's maneuver; then subacute uterine inversion by Haultain's operation (cervical ring is posteriorly incised to facilitate uterine replacement by Huntington method). 5,6 Another case report of successful management of recurrent puerperal uterine inversion was managed first by Jhonson's maneuver for acute inversion and for recurrent uterine inversion exploratory laparotomy was done to reposit by Huntington technique (progressive upward traction on each round ligament by application of atraumatic clamps with simultaneous upward pressure transvaginally) and multiple Cho suture; bilateral uterine arteries and utero ovarian arteries were ligated prophylactically. Vaginal pack with roller gauze kept prophylactically to prevent reinversion.…”
Section: Commentsmentioning
confidence: 99%